16.7k views
3 votes
Write a trinomial expression that is equivalant to the following product?
(3x-2)(2x-11)

User Rickkwa
by
5.1k points

2 Answers

0 votes

Answer:

6x^2 - 37x + 22

Explanation:

User JG Estiot
by
6.0k points
2 votes

6x^2 - 37x + 22

Use the FOIL method to multiply the binomials.

First monomial in each binomial: 3x * 2x = 6x^2

Outside monomials: 3x * -11 = -33x

Inside monomials: -2 * 2x = -4x

Last monomial in each binomial: -2 * -11 = 22

Now, just add: 6x^2 - 33x - 4x + 22 = 6x^2 - 37x + 22

User Raul Santelices
by
5.3k points